упростите не используя формулу радикала √(9-4√2) -√(3+2√2)

0 голосов
51 просмотров

упростите не используя формулу радикала

√(9-4√2) -√(3+2√2)

Алгебра (65 баллов) | 51 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

Решите задачу:

\sqrt{9-4\sqrt{2}}-\sqrt{3+2\sqrt{2}}=\\\\\sqrt{8-4\sqrt{2}+1}-\sqrt{1+2\sqrt{2}+2}=\\\\\sqrt{(2\sqrt{2})^2-2*(2\sqrt{2})*1+1^2}-\sqrt{1^2+2*1*\sqrt{2}+(\sqrt{2})^2}=\sqrt{(2\sqrt{2}-1)^2}-\sqrt{(1+\sqrt{2})^2}=\\\\|2\sqrt{2}-1|+|1+\sqrt{2}|=\\\\2\sqrt{2}-1-1-\sqrt{2}=\sqrt{2}-2

(409k баллов)
0 голосов

=(2sqrt(2)-1)-1(+sqrt(2))=sqrt(2)-2

(232k баллов)